2002
DOI: 10.1046/j.1473-6861.2002.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Capturing expertise in the development of practice: methodology and approaches

Abstract: This study employed two distinct methodologies: 18 months of participant observation whilst working as a nurse and invited observations of episodes of skilled behaviour followed by knowledge interviews using heuristic devices as mediating artefacts. Access to the ward and invitations to observe (with patient consent) were granted in return for free labour between episodes and whenever the ward was exceptionally busy. The ethnographic data was analysed using Strauss’s paradigm analysis; the resultant accounts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Just as proposed in these theories we found that the amount of templates chunked into an expert's memory is a function of the amount of incidents they have attended in the past, their years of experience and their level of exposure to difficult tasks -through which they are then able to build up a reservoir of recognized pattern (see Table 1). Previous studies have shown that the more patterns people are able to acquire over their years of practice, the more they are able to match a new situation to one of the patterns stored in their reservoir of knowledge (Shanteau, 1992;Zsambok, 1997;Eraut, 2000;Fessey, 2002;Rosen, Shuffler, and Salas, 2010). This explains why fire fighters, in real life, could see the colour of a smoke and intuitively know that toxic chemicals and other combustible materials are involved.…”
Section: Creative Decisionsmentioning
confidence: 91%
See 2 more Smart Citations
“…Just as proposed in these theories we found that the amount of templates chunked into an expert's memory is a function of the amount of incidents they have attended in the past, their years of experience and their level of exposure to difficult tasks -through which they are then able to build up a reservoir of recognized pattern (see Table 1). Previous studies have shown that the more patterns people are able to acquire over their years of practice, the more they are able to match a new situation to one of the patterns stored in their reservoir of knowledge (Shanteau, 1992;Zsambok, 1997;Eraut, 2000;Fessey, 2002;Rosen, Shuffler, and Salas, 2010). This explains why fire fighters, in real life, could see the colour of a smoke and intuitively know that toxic chemicals and other combustible materials are involved.…”
Section: Creative Decisionsmentioning
confidence: 91%
“…The excerpts in table 3 demonstrate how participants reported this experience-based prototypical decision making strategy: As shown in Table 3 all the expert participants agreed that dealing with a current problem often requires making use of previous knowledge and experiences, mainly by matching cues from the environment to the numerous patterns that have been pre-stored in the memory. Prior research has evidenced how experienced commanders develop domain knowledge from the consistent and repeated experiences they have linked together unconsciously to form a pattern (Crandall and Gretchell-Leiter, 1993;Fessey, 2002;Hogarth, 2003;Klein, 2003;Perry and Wiggins, 2008). A pattern therefore represents a set of "action scripts" that is chunked together and often triggered by one or more internal or external cues.…”
Section: Creative Decisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is substantial evidence to demonstrate that experiences gained in real-life (on-the-job) practice settings have the potential of making more important contributions that cannot be afforded by experiences in other settings (c/f Klein, 2003). Learning should therefore be seen as an ongoing activity for less-experienced personnel as well as a crucial part of their daily thinking and acting 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 (Fessey, 2002). This way, novices are made to learn the most current, tailored and up-to-date skills based on the constantly changing environment typical of most high risk organizations.…”
Section: Resultsmentioning
confidence: 99%
“…This is because experts can unintentionally misrepresent the conceptual knowledge upon which their competence is based: a paradox where professionals are able to refer to scientific data, theoretical manuals and standard operational procedures (SOPs) in clear explicit terms, yet using the same factual knowledge tacitly (Eraut, 2004;Fessey, 2002;Spender, 2008;Feldon, 2007). On this note, it therefore seems that experts' performance is qualified by another type of knowledge i.e.…”
Section: Introductionmentioning
confidence: 99%